Population Structure of Rhododendron Campanulatum D. Don and Associated Tree Species along the Elevational Gradient of Manaslu Conservation Area, Nepal - Rana, Prabina; Koirala, Madan; Bhuju, Dinesh Raj; Boonchird, Chuenchit (Journal of Institute of Science and Technology, 2016)
Climate change is affecting the forest ecosystems worldwide. Impacts of climate change are more perceptible at higher altitudes and can be easily detected along the elevational gradient. The main aim is to study the impact of elevation on the population structure of Rhododendron campanulatum D. Don and associated trees species at Manaslu Conservation Area, central Nepal. A total of 30 quadrats were sampled from 3600-4100 meter above sea level (m asl.) at altitudinal difference of 100 m with 5 quadrates in each altitude. The present study showed that R. campanulatum, Betula utilis, Abies spectabilis and Sorbus microphylla are the treeline species. R. campanulatum was the most dominant species with highest importance value index (IVI) along the altitudinal gradient. At 4000 m asl. S. microphylla was the codominant species. B. utilis was the codominant species at 3600 -3900 m asl followed by S. microphylla and A. spectabilis. R. campanulatum and A. spectabilis showed a sustainable regeneration. No seedling of B. utilis was found along the altitudinal gradient indicating that the regeneration of this species might be affected by unfavourable micohabitat (eg. deep shade). R. campanulatum and S. microphylla were found above the treeline indicating that the climatic conditions were favourable for their growth. The height, diameter and density of the species differed along the elevational gradient and showed a species specific trend. Journal of Institute of Science and Technology Vol. 21, No. 1, 2016, page: